MEROPENEM IMPRINTED POLYMER AS SELECTIVE SORBENT FOR SOLID PHASE EXTRACTION METHOD FOR MEROPENEM ANALYSIS IN HUMAN BLOOD PLASMA - Sirumapea, Lasmaryna
Meropenem is antibiotic of carbapenem group, which has beta-lactam ring on its main structure. Meropenem is given to treat many kinds of infection caused by bacteria, and also to treat fever that followed by the decrease of leucosyt. This kind of antibiotic is not over the counter medicine, it is given only on doctor’s presciption. Meropenem is an antibiotic that has high sensitivity on many kinds of microbes. The role of analytical methods is very important in the success of drug analysis in biological matrices. Sensitivity of analytical method has to be high, because a drug usually present in the plasma in a small amount. Analytical method has to be selective due to the existence of other compounds, which can interfere the analysis. Solid phase extraction is one type of sample preparation that uses sorbent. Until now, sorbent for solid phase extraction of meropenem is still a conventional sorbent and has not been made with a molecular imprinting technique. Meropenem is an antidiabetic drug with a betalactam ring in its main structure. Methacrylic acid (MAA) and acrylamide (ACR) monomer has never been reported as a functional monomer in molecular imprinted polymer. The aim of this study was to have a solid phase extraction sorbent for meropenem by using molecular imprinted techniques using meropenem as a template molecule or commonly known as molecular imprinted polymer solid phase extraction (MI- SPE). The sorbent was used to increase the separation efficiency of meropenem in biological matrices.